2016
DOI: 10.1084/jem.20160526
|View full text |Cite
|
Sign up to set email alerts
|

Microbial antigen mimics activate diabetogenic CD8 T cells in NOD mice

Abstract: Wen et al. show that there are gut microbial antigens sharing significant homology with the host pancreatic protein peptide IGRP and that can drive self-reactive T cell activation and accelerate diabetes in NOD mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 47 publications
2
117
0
1
Order By: Relevance
“…Turley has reported that PLNs drain antigens from both pancreas and intestine [32]. In line with this observation, we recently found a commensal microbial antigen that can be recognized by diabetogenic T cells, which in turn attack islet beta cells [33]. Similar results were also observed in an autoimmune uveitis model [34].…”
Section: Nod2supporting
confidence: 86%
“…Turley has reported that PLNs drain antigens from both pancreas and intestine [32]. In line with this observation, we recently found a commensal microbial antigen that can be recognized by diabetogenic T cells, which in turn attack islet beta cells [33]. Similar results were also observed in an autoimmune uveitis model [34].…”
Section: Nod2supporting
confidence: 86%
“…These findings strongly support a need for a TCR-driven signal, perhaps from a microbiota-derived antigenic mimicry, but they do not negate a requirement for innate adjuvant effects, which also can come from microbiota. Although the putative antigenic mimic in uveitis has not been identified, a mimic of an antigen responsible for type 1 diabetes was recently reported (11). Thus, antigenic mimicry by commensals may be a more common and frequent trigger of autoimmune diseases than it is currently appreciated.…”
mentioning
confidence: 99%
“…Conversely, there has been speculation that gut bacteria may trigger T1D development in genetically susceptible humans (45) and mouse models of T1D (46). One possible means by which this could occur could be transfer of metabolites or cell components of the bacteria through a “leaky” gut wall and uptake by antigen presenting cells, processing and presentation of the antigen to activate T cells (47).…”
Section: Modification Of the Gut Microbiotamentioning
confidence: 99%
“…Alterations in intestinal permeability allow access of bacterial toxin (45), infectious agents and dietary antigens from the lumen to mucosal immune elements (48, 49). Another possible mechanism is some bacterial product(s) share the molecular homology with islet autoantigen(s) and the islet beta cells are attacked by the immune cells that are reactive to the bactierial antigens (46). …”
Section: Modification Of the Gut Microbiotamentioning
confidence: 99%